Brexit or Corbyn? Campaign and Inter-Election Vote Switching in the 2017 UK General Election. Issue 4 (5th February 2018) - Mellon, Jonathan; Evans, Geoffrey; Fieldhouse, Edward; Green, Jane; Prosser, Christopher
Abstract: The 2017 UK General Election saw the collapse of UKIP and an unusually influential campaign that saw Labour improving from a likely historic defeat to almost pulling level with the Conservatives, denying Theresa May a parliamentary majority. We argue that the election should be understood in two phases: first from 2015 to the start of the election campaign, and second the campaign itself. The former period was characterised by strong switching along Brexit lines, with 2015 UKIP voters defecting heavily to the Conservatives following the outcome of the EU Referendum, which had enabled the Conservatives to make credible promises on immigration. Concurrently, many 2015 Labour supporters had defected to other parties or were undecided. The campaign then saw Labour winning voters from all sources, but particularly from previously undecided voters. While campaign vote flows were not as strongly related to Leave/Remain votes, 2015–2017 switching as a whole was heavily influenced by the EU referendum choices. We conclude that 2017 was indeed a 'Brexit election', but the campaign is better understood as a general rise in support for Labour resulting from Corbyn's appeal relative to that of Theresa May, particularly among the party's own 2015 voters who had defected before the campaign.